(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper has been attempted to understand and analyse the key factors which influence consumer behaviour for online shopping. The study of consumer behaviour towards online shopping provides various information such as what motive prompt consumer to make purchase so that same are utilised in promotional campaigns to awaken desire to purchase in the mind of consumer and knowledge of consumer behaviour will be useful to the marketers. Thus study of consumer behaviour is important to understand the changes in taste, preferences and attitude of consumer while doing online shopping. For achieving the objectives of the study primary data has been taken by the researcher.